2022
DOI: 10.1021/acsomega.2c02712
|View full text |Cite
|
Sign up to set email alerts
|

Skillful Introduction of Urea during the Synthesis of MOF-Derived FeCoNi–CH/p-rGO with a Spindle-Shaped Substrate for Hybrid Supercapacitors

Abstract: A composite (FeCoNi–CH/p-rGO) with a spindle-shaped substrate is controllably prepared by combining FeCoNi carbonate hydroxide (FeCoNi–CH) and partially reduced graphite oxide (p-rGO) using a novel chemical strategy. In the synthetic process, urea is introduced as the precipitant and reducing agent. MIL-88A as a self-template is converted into a ternary-metal CH composite, maintaining the original morphology by the metal ion etching and coprecipitation method, and graphite oxide is reduced to rGO with stronger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 64 publications
(103 reference statements)
0
5
0
Order By: Relevance
“…It demonstrates that there are other forms of O present. Figure S2 illustrates the FT-IR results of MD 3 , with peaks observed at 1634 and 1400 cm −1 corresponding to the symmetric and asymmetric stretching modes, respectively, of the carboxyl groups in 2,6-NDC [ 32 ]. Furthermore, the fact that the derivative retained the basic shape of the precursor also indicated that the organic ligand had not completely collapsed.…”
Section: Resultsmentioning
confidence: 99%
“…It demonstrates that there are other forms of O present. Figure S2 illustrates the FT-IR results of MD 3 , with peaks observed at 1634 and 1400 cm −1 corresponding to the symmetric and asymmetric stretching modes, respectively, of the carboxyl groups in 2,6-NDC [ 32 ]. Furthermore, the fact that the derivative retained the basic shape of the precursor also indicated that the organic ligand had not completely collapsed.…”
Section: Resultsmentioning
confidence: 99%
“…The specific capacitance (C, F g −1 ) of the materials was calculated by using the Equation (3), where I (A), ∆t (s), m (g), and ∆V (V) are discharge current, discharge time, mass of active material, and potential window, respectively. [48]…”
Section: Methodsmentioning
confidence: 99%
“…As can be seen, the charge–discharge profiles of the MO-rGO||MOF-LDH device at lower rates consist of three regions: two sloping parts at high and low voltage ranges along with a voltage plateau with a moderate slope in between. Such a GCD profile reflects the dual supercapacitor–battery character of the MO-rGO||MOF-LDH device in which the steeper slope regions indicate the capacitive behavior and the moderate-slope region explains the battery-like character of the materials . Note, however, that at extremely high current values, the capacitive behavior dominates the mechanism due to the slow kinetics of the Faradaic processes at exceedingly high specific current values.…”
Section: Mo-rgo||mof-ldh Superbattery Assemblymentioning
confidence: 99%
“…Such a GCD profile reflects the dual supercapacitor−battery character of the MO-rGO||MOF-LDH device in which the steeper slope regions indicate the capacitive behavior and the moderate-slope region explains the battery-like character of the materials. 94 Note, however, that at extremely high current values, the capacitive behavior dominates the mechanism due to the slow kinetics of the Faradaic processes at exceedingly high specific current values. The device exhibits a high specific capacity of 47.3 mA h g −1 (specific capacitance of 118.2 F g −1 ) at a specific current of 1 A g −1 .…”
Section: ■ Mo-rgo||mof-ldh Superbattery Assemblymentioning
confidence: 99%
See 1 more Smart Citation